De Novo Mutation of KAT6B Gene Causing Atypical Say–Barber–Biesecker–Young–Simpson Syndrome or Genitopatellar Syndrome. (4th March 2017) - Li, Guoqiang; Li, Niu; Li, Juan; Ding, Yu; Yu, Tingting; Wang, Xiumin; Wang, Jian
ABSTRACT: Mutations in KAT6B gene are responsible for Say–Barber–Biesecker–Young–Simpson syndrome (SBBYSS) and genitopatellar syndrome (GPS), with most mutations occurring in exon 18. A 4-year-old Chinese boy presented with short stature but no other clinical features of SBBYSS or GPS had a de novo novel nonsense pathogenic mutation in exon 14 of the KAT6B gene at position c.2636T>A (p.Leu879X). The correlation analysis of genotype–phenotype indicated distinctive clinical features (short stature, growth hormone deficiency, and delayed bone age) compared with the classical mutations of KAT6B gene. To the best of our knowledge, this is the first report of KAT6B gene mutation in any Chinese individual. This work expands the mutant phenotypic spectrum of the KAT6B gene.